Spear of the Nation : Umkhonto weSizwe - Cherry, Janet (Book collections on Project MUSE., 2012)
Umkhonto weSizwe, Spear of the Nation, was arguably the last of the great liberation armies of the twentieth century-but it never got to "march triumphant into Pretoria." MK-as it was known-was the armed wing of the African National Congress, South Africa's liberation movement, that challenged the South African apartheid government. A small group of revolutionaries committed to the seizure of power, MK discovered its principal members engaged in negotiated settlement with the enemy and was disbanded soon after. The history of MK is one of paradox and contradiction, of successes and failures.